(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses the history of the Russian language, the modern and ancient Russian (East Slavic) language, the views of linguists in its development, the role of the Russian language in the world and its teaching in schools and universities in many countries.